Biofortification mainstreamed into national breeding programs in Bangladesh, India, and Rwanda through partnerships between HarvestPlus and National Agricultural Research and Extension Systems (NARES) - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
An external review of the development of national biofortification breeding programs in Bangladesh for zinc rice, India for iron pearl millet, and Rwanda for iron beans described how and to what extent HarvestPlus contributed to the establishment and implementation of sustainable biofortification breeding programs. The study documented the HarvestPlus investment in national partners to undertake biofortification breeding and concludes that without this investment, it is highly unlikely that the biofortification breeding programs would have been established.